An examination of the association between premature mortality and life expectancy among men in Europe - White, A. (2013)
A feature of the health of men across Europe is their higher rates of premature mortality and shorter life expectancy at birth than women. Following the publication of the first State of Men's Health in Europe report, we sought to explore possible reasons.